Safety and feasibility of toripalimab plus lenvatinib with or without radiotherapy in advanced BTC - Wang, Yunchao; Zhang, Nan; Xue, Jingnan; Zhu, Chengpei; Wang, Yanyu; Zhang, Longhao; Yang, Xu; Wang, Hao; Wang, Shanshan; Chao, Jiashuo; Yang, Xiaobo; Zhao, Haitao (Frontiers in Immunology, 2023)
Background: Toripalimab shows antitumor efficacy in cholangiocarcinoma. Radiotherapy (RT) may enhance systemic responses of PD-1 inhibitors and lenvatinib. This study was designed to assess the safety and feasibility of toripalimab plus lenvatinib with or without RT in advanced BTC. Methods: This study involved 88 patients with advanced BTC receiving toripalimab plus lenvatinib with or without RT from the clinical trials (NCT03892577). Propensity score matching (PSM) (1:1) analysis was used to balance potential bias. The overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and adverse events (AEs) were evaluated. Results: After PSM, the final analysis included 40 patients: 20 receiving toripalimab plus lenvatinib without RT (NRT); 20 receiving toripalimab plus lenvatinib with RT. The AEs were more frequent in the RT group than in the NRT group without treatment-associated mortality. The addition of RT did not cause specific AEs. The median PFS was significantly longer with RT (10.8 versus 4.6 months, p<0.001). The median OS was 13.7 months with RT versus 9.2 months in the NRT group (p=0.008). The ORR was 35% (95% CI: 12.1-57.9) in the RT group versus 20% (95% CI: 0.8-39.2) in the NRT group. Conclusions: The addition of RT may enhance the efficacy of toripalimab plus lenvatinib. Toripalimab plus lenvatinib with RT have a good safety profile without an increase in specific toxicities in advanced BTC patients.